‘United Nations’, ‘United Church’ - Norwood, Donald W. (Theology, 2010)
AbstractAlmost from its inception 100 years ago the modern ecumenical movement saw the vocation of Christian unity as including witness for world peace. Today the World Council of Churches and the United Nations, both officially inaugurated in 1948, share a common concern albeit on distinct bases and with different methods. In fact there was profound Christian influence upon the UN in its formation and in its subsequent leadership, while in turn the UN takes seriously the WCC as a major resource for thinking and action for peace, justice and human rights, and this expectation from the UN must be taken seriously by the churches and their theologians.